IMPLEMENTASI METODE FUZZY LOGIC PADA SISTEM PAKAR PENDETEKSI KECERDASAN ANAK - Devira Asha; Muhamad Bahrul Ulum; Yuli Asmi Rozali (Jurnal Komputasi, 2021)
The multiple intelligences proposed by Dr. Howard Gardner in his book entitled Frame of Mind states that every child has unique and different characteristics and does not only focus on one intelligence. Parents who don't know how to improve their children's intelligence from all categories of intelligence, and only focus on language and logic intelligence, are considered as intelligent benchmarks for children. This expert system application aims to facilitate parents in knowing the level of intelligence of children so that children get the opportunity to develop at least from various dimensions such as musical, kinesthetic, intra and interpersonal, etc. This study applies calculations using the Mamdani fuzzy logic method. The results of this study are able to identify children's intelligence by designing a fuzzy expert system where input variables and output variables are generated from interviews with experts who produce 45 input variables and 9 outputs. For example, the calculation in this study uses 5 input variables and 1 output variable with the number of rules generated, namely 243 rules. The results obtained from the manual calculation of the fuzzy logic method are 50.68 with a fairly intelligent level of medium level. The system development method used in this research is the extreme programming method with the Laravel framework. This website-based expert system application is also a place for information on multiple intelligences where this information will be useful to find out how to improve children's intelligence from all categories of intelligence.